Mechanically induced single-molecule white-light emission of excited-state intramolecular proton transfer (ESIPT) materials. Issue 5 (10th March 2021) - Huang, Quan; Guo, Qiang; Lan, Jingbo; Su, Rongchuan; Ran, You; Yang, Yudong; Bin, Zhengyang; You, Jingsong
Abstract : Disclosed herein is the first example of a mechanically induced single-molecule white-light emission of ESIPT materials. Mechanical grinding transforms intermolecular packing motifs, enabling emission color switching from yellowish green to white. Abstract : Described herein is the first example of mechanically induced single-molecule white-light emission based on excited-state intramolecular proton transfer (ESIPT) materials. The mechanism of mechanochromism is clearly disclosed by powder and single crystal X-ray diffraction (XRD) data, infrared spectroscopy, and fluorescence up-conversion measurement, etc. 2-(2′-Hydroxyphenyl)oxazole (6b) with a herringbone packing motif exhibits a predominant keto-form emission, giving off yellowish-green fluorescence. Mechanical grinding transforms the herringbone packing motif into a brickwork packing motif, decreases the intermolecular distances, which results in an enhanced intermolecular charge-transfer interaction, and therefore changes the ESIPT dynamics, leading to an enhanced enol-form emission and white fluorescence. Herringbone-packing 6b is thermodynamically more stable than brickwork-packing 6b. Thus, the latter can convert to the former by solvent fuming or thermal annealing.